Helminth communities in the alimentary tract of free raised chickens on rainfed and irrigated agrosystems from southwest Spain - M. N. García Cuadrado (Taylor & Francis Group, 2021)
The helminth communities of Extremeña Azul breed chickens (Gallus gallus) have been studied from south-western free-ranging farms in Spain. Two farming systems were compared: a rainfed system and an irrigated system. Necropsy was applied to the animals to compare the structure, biodiversity, and evolution of helminth communities as well as to determine the correlation between parasite burden and chicken weight. 12 species of parasites were identified: 7 cestodes (Raillietina echinobothrida, R. tetragona, Skrajabinia cesticillus. Echinolepis carioca, Davainea proglottina, Amoebotaenia cuneata and Choanotaenia infundibulum), and 5 nematodes (Heterakis gallinarum, Ascaridia galli, Baruscapillaria obsignata, Eucoleus annulatus, and Aonchotheca caudinflata). Cestode prevalence was 54% in the rainfed system whereas it was 98% in the irrigated system; nematode prevalence was 100% in both communities. There were 2 core species in the rainfed and 5 in the irrigated system. The rainfed community showed lower species richness and more dominance. In the irrigated system, the helminth community showed higher biodiversity than in the rainfed system community. This could be attributed to the abundance of intermediate hosts due to irrigation. This study provides data on the distribution of chicken helminths in south-western Europe and the influence of the farming system on their biodiversity.Highlights Helminth communities of free-ranging chickens from two different organic agrosystems (irrigated and rainfed) are compared in southern Spain. The irrigated system showed the highest prevalence of helminths. Eucoleus annulatus was only observed in this system with a prevalence of 98%. This is the first study carried out in Spain about this issue. It may be of interest to poultry organic farmers.